Quality of Information Management in The Opinion of Managers and Staff of The Organization - Marian KOPCZEWSKI; Zbigniew GROBELNY; Małgorzata WILCZYNSKA; Grzegorz WISNIEWSKI (Communications of International Proceedings, 2023)
Information management is a process that plays an important role in all interpersonal relationships. It accompanies man from the moment when man began to live in groups and organize the first structures. It is hard to imagine a modern society, especially a military one, whose members do not properly manage information. The transfer and exchange of information is also very important in the activities of any organization. Therefore, the diagnosis of the information quality management system in the organization significantly affects the effectiveness of management. The article contains a detailed assessment of the information quality management process in the opinion of managers and subordinates /employees/. The basis for a modern approach to information quality management should be building contacts between the organization and its customers, while the basis for creating proper contacts with customers is the information quality management system. Communication in this sense should be two-way, not just one-way. Information management is not only providing information, but also creating a community when providing information about the state of security. The research was carried out in 10 logistic units, the main objective was to examine the impact of the quality of information on the effectiveness of management. The survey was presented to the respondents in order to obtain an accurate picture of the information quality management process between individual key organizational units in the organization that affect the security of the organization.
Keywords: Information; management; organization